SURVEI TINGKAT VO2MAX PADA SISWA YANG MENGIKUTI EKSTRAKURIKULER SEPAK BOLA DI SMA NEGERI 3 PEKANBARU - Saputra, Afrizal; Ramadi, Ramadi; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The aim of this research is to determine the VO2Max level survey ofstudents who take part in football extracurriculars at SMA Negeri 3 Pekanbaru. Thesample was taken as a whole from the Pekanbaru City 3 Public High School foot ballteam, totaling 20 students. The method used is a survey with data collection techniquesusing tests and measurements. This research aims to determine the VO2Max levelsurvey of students who take part in extracurricular football at SMA Negeri 3Pekanbaru. From the results of the VO2Max analysis of students who take part in football extracurriculars at SMA Negeri 3 Pekanbaru as a whole, it can be concluded thatthe endurance results or Vo2max of students who take part in extracurricular foot ballat SMA Negeri 3 Pekanbaru are in the very poor category, namely 17 out of 20 studentsare <35. which is around 85%. 15% are in the poor category or around 3 people out of20 who get a score in the range of 35-38.Key Words: Vo2max Level Survey, Foot ball Extracurricular